Exploring the Impact of Brand Image on Consumer Loyalty - Sabir Sadiq Abdulkhaliq; Murad Muzafer Hamze (مجلة الغري للعلوم الاقتصادية والادارية)
The main objective of this study is to investigate the impact of brand image on consumer loyalty towards users of computer products in the Kurdistan region universities. To achieve the objective of the study, a quantitative method based on purposive sampling was conducted. A total of 312 online surveys were collected from students and university members who use different computer products in universities in the four provinces of Erbil, Dohuk, Sulaymaniyah, and Halabja in the Kurdistan Region of Iraq. Structural Equation Modeling (SEM) with the help of the Partial Least Squares (PLS) method and the PLS software was used to test the hypotheses and validate the model. The result of the study revealed that brand image has a significant impact on consumer loyalty. The results also show that while brand associations, may not always significantly predict consumer loyalty, other dimensions such as brand personality, brand emotions, and brand experience have a profound positive impact on the findings of this study.